The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1136/gutjnl-2014-307173
|View full text |Cite
|
Sign up to set email alerts
|

Training and competence assessment in GI endoscopy: a systematic review

Abstract: The use of validated VR simulators in the early training setting accelerates the learning of practical skills. Learning curves are valuable for the continuous assessment of performance and are more relevant than threshold numbers. Future research will strengthen these conclusions by evaluating simulation-based as well as patient-based training in GI endoscopy. A complete curriculum with the assessment of competence throughout training needs to be developed for all GI endoscopy procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
121
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(131 citation statements)
references
References 102 publications
(117 reference statements)
2
121
0
2
Order By: Relevance
“…One study even showed that a well-validated video trainer for assessment of laparoscopic skills was superior to a high-cost virtual reality system 3. Our concept would therefore nicely complement haptic simulators systematically reviewed by Ekkelenkamp et al 1 in blended training approaches to invasive procedure training, which have been shown to improve trainee skills 4. Residency and fellowship directors may consider adding computer devices, multimedia content and introduce blended learning to their respective training programmes.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…One study even showed that a well-validated video trainer for assessment of laparoscopic skills was superior to a high-cost virtual reality system 3. Our concept would therefore nicely complement haptic simulators systematically reviewed by Ekkelenkamp et al 1 in blended training approaches to invasive procedure training, which have been shown to improve trainee skills 4. Residency and fellowship directors may consider adding computer devices, multimedia content and introduce blended learning to their respective training programmes.…”
mentioning
confidence: 89%
“…We read with interest the paper by Ekkelenkamp et al ,1 who found that the early use of validated simulators during endoscopy training expedites the learning of procedural skills.…”
mentioning
confidence: 99%
“…There is a move away from a numbers-based criteria and towards competency-based assessment. A recent systematic review concluded that "learning curves are valuable for the continuous assessment of performance and are more relevant than threshold numbers" [4]. Ideally, several components of any skill should be assessed and each component should have a clear descriptor to minimise the influence of assessment biases.…”
Section: Training and Assessment Of Endoscopy Skillsmentioning
confidence: 99%
“…Competence in colonoscopy requires experience with 150-200 colonoscopies under supervision (Ekkelenkamp et al 2016). That competence improves with practice is not surprising and known from, for instance, in chess (De Groot 1978).…”
Section: Clinical Reasoning and The Development Of Expert Performancementioning
confidence: 99%